Profil Pengobatan Dan Efektivitas Obat Tuberkulosis Paru Pada Pasien Tuberkulosis Paru Di Puskesmas Kebayoran Lama - Rahajeng, Suny Koswara; Sayyidah, Sayyidah; Fadhilah, Humaira; Dewantoro, Agung; Dewi, Bheta Sari; Ardiansyah, Muhammad Rivan (PHRASE (Pharmaceutical Science) Journal, 2025)
Pulmonary tuberculosis (TB) is a serious health problem in Indonesia. A treatment profile that meets guidelines and patient compliance is crucial for successful therapy. To determine the treatment profile and effectiveness of TB drugs in patients at the Kebayoran Lama Community Health Center. This descriptive study used secondary data from the medical records of 78 pulmonary TB patients selected by purposive sampling from July to December 2024. Analysis was based on patient characteristics, treatment profiles, and drug effectiveness. The results the majority of patients were aged 17-25 years (38%), female (51%), had a high school education (54%), and worked as private sector workers (27%). In the intensive phase, most patients (72%) weighing 55-70 kg received a regimen of 4 tablets of 4FDC; the continuation phase used 4 tablets of 2FDC. The effectiveness of therapy was demonstrated by 54% of patients with negative AFB conversion accompanied by clinical improvement (reduced cough, increased appetite, decreased shortness of breath). The Conclusion is Pulmonary TB treatment at the Kebayoran Lama Community Health Center is in accordance with national guidelines with weight-based dosage. Regular evaluation is still needed to improve the success of therapy.